"It's our children!" Exploring intersectorial collaboration in family centres. Issue 4 (8th May 2018) - Bulling, Ingunn Skjesol; Berg, Berit
Abstract: Services providing support for children and families are often described as fragmented and more concerned with the boundaries of their fields of responsibility than collaborating with other sectors. To meet the need for greater collaboration, there is increased impetus for establishing interdisciplinary services, such as family centres. This paper presents the results of a qualitative study based on in‐depth interviews and participant observation in 3 Norwegian family centres. The findings provide insight into central challenges in developing new practices within the field of family support; we discuss how intersectorial collaboration is constructed in relation to the core objectives of the family centre, professional competence, and service stability. This study demonstrates that both managers and professionals struggle with prioritizing intersectorial work, which mainly focuses on prevention and health promotion, over and above their traditional sectoral responsibilities. It also illustrates the necessity of articulating intersectorial collaboration as an explicit aim and exploring its implications and examining how this contributes to family centres building supportive communities. Building integrated services is not the ultimate goal of this particular form of service provision but rather the first step towards building interconnected support systems for all children in the community.